VIABILITAS SPERMATOZOA PETAURUS BREVICEPS PAPUANUS T. - SUARNI, NI MADE RAI; ERMAYANTI, I GUSTI AYU MANIK (Jurnal Biologi Udayana; Vol 13 No 2 (2009): JURNAL BIOLOGI, 2009)
Experiment to determine the spermatozoa viability of Petaurus berviceps papuanus T. has been performed. Observation was done under microscope and trypan blue was used as stain. Viable spermatozoa were counted from a total of 100 spermatozoa. It was found that 4,75 % of the spermazoa could be maintained for 7.5 hours in the DMEM (Dulbecco's modified Eagle's medium) at 35oC.
Keywords: Petaurus berviceps papuanus T., spermatozoa, viability